Co‐teaching in a mainstream post‐primary mathematics classroom: an evaluation of models of co‐teaching from the perspective of the teachers. Issue 2 (21st September 2018) - Carty, Audrey; Marie Farrell, Ann
Abstract : This article examines the use of a range of co‐teaching models when teaching mathematics. The approaches suggested have potential for all students, but in this instance their importance as a pedagogical approach with students with special educational needs (SEN) in inclusive classrooms is considered. The study was based in the first‐year mathematics classroom of an Irish, urban, mainstream, post‐primary, girls' school. This article highlights the findings from the teacher's perspective and presents their reflections on a range of co‐teaching approaches. The potential and challenges of these are considered in the context of schools generally.